Integrating broccoli rotation, mustard meal, and anaerobic soil disinfestation to manage verticillium wilt in strawberry. (August 2021) - Zavatta, Margherita; Muramoto, Joji; Milazzo, Elizabeth; Koike, Steven; Klonsky, Karen; Goodhue, Rachael; Shennan, Carol
Abstract: Verticillium wilt, a disease caused by the fungus Verticillium dahliae, affects a vast range of crops, including strawberries. A field trial was established to evaluate the effect of broccoli in rotation prior to strawberries, anaerobic soil disinfestation (ASD), and mustard cake (MC) alone and in combination at suppressing V. dahliae. Broccoli, cauliflower and fallow plots were established in year 1, followed by strawberry, winter cover crop, and lettuce across all plots over the next two years. ASD and ASD + MC improved strawberry yields compared to the untreated control (UTC). At the end of the harvest season, V. dahliae infection rates in strawberry crowns were lower in the ASD and ASD + MC treatments compared to the UTC. After harvest of the lettuce crop, the number of V. dahliae microsclerotia in soil treated previously with ASD was lower than in the UTC. Broccoli residue incorporation had no effect and MC alone a limited effect on strawberry yields, V. dahliae in strawberry crowns, and soil microsclerotia levels at lettuce harvest. All rotations treated with ASD showed higher total net returns despite the higher cost of treatments. The ability of ASD to control V. dahliae and its persistent suppressive effect on soil microsclerotia levels have important economic implications for growers. Highlights: ASD lowered V. dahliae infection rate in strawberry plants while increasing yield. ASD disease suppression effect in the soil was still present after a rotation with lettuce two years after the treatment. Rotation with broccoli had higher net returns than other rotations when averaged across treatments. MC provided limited disease suppression.